Mapping key actors in family support. A European perspective - Jiménez García, Lucía; Canavan, John; Baena, Sofía; Herrera-Pastor, David; Lloyd, Andrew; Schima, Johanna; Grasmeijer, Jean (Elsevier, 2024)
Research has proven that family is the context for the development and well-being of the new generation, and parents need support in order to fulfill children and young people’s physical, cognitive, emotional, and social needs. Most EU policy relating to children and young people is mediated through family even if this is not explicitly named. At a national level, European countries have been encouraged to offer family support initiatives through local authorities that promote positive parenting and guarantee children’s rights. The current challenge in the family support landscape consists of engaging the European level with the local and national structures, in order to support the delivery of quality family support systems and services across Europe. This article reports on the progress in this area by the European Family Support Network (EurofamNet). EurofamNet was created with the purpose of establishing a pan-European family support network to inform family support policies and practices in order to contribute with global actions to face current challenges in family support agenda at European level. This paper introduces the mapping exercise performed by the network to identify key family support actors for research, policy, and practice at the European, local and national level. For this purpose, an expert-targeted approach was followed. Two experts identified 83 key family support actors at the European level, and a panel of 22 experts jointly identified 326 key actors and organizations in 17 European countries. The analysis of this mapping exercise offers an interesting mosaic of family support provision in different European countries that reflect both intra- and inter-network diversity in nature, scope, and sectors of family support actors and organizations.

At the same time, this mapping exercise contributes to creating social fabric with the potential to facilitate knowledge mobilization of quality standards to be implemented for the guarantee of quality provision in family support in Europe. Practical implications for the development of the family support and wider services fields of this novel initiative of connecting the efforts of key actors in family support throughout Europe are discussed.
This article is based upon work from COST Action CA18123 The European Family Support Network, supported by COST (European Cooperation in Science and Technology). It was funded by a Virtual Mobility Grant (E-COST-GRANT-CA18123-2bfb80ed) awarded by the abovementioned COST Action.
Keywords: Familias - Países de la Unión Europea; Educación familiar; Niños - Desarrollo; Europa - Política familiar; Family support; Evidence-based practice; Network; Europe; Quality assurance; Knowledge mobilization